2020
DOI: 10.1371/journal.pone.0233575
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of prediction models in relapsing remitting multiple sclerosis

Abstract: The natural history of relapsing remitting multiple sclerosis (RRMS) is variable and prediction of individual prognosis challenging. The inability to reliably predict prognosis at diagnosis has important implications for informed decision making especially in relation to disease modifying therapies. We conducted a systematic review in order to collate, describe and assess the methodological quality of published prediction models in RRMS. We searched Medline, Embase and Web of Science. Two reviewers independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 67 publications
(198 reference statements)
4
41
0
Order By: Relevance
“…As clinical outcomes, we selected the EDSS score, the most widely validated MS disability measure, which was used in all prognostic studies, 6 , 7 , 9 - 12 , 14 , 15 and evolution to SPMS, that is associated with a poor prognosis, mostly because of the limited DMT effect in these patients. During the 6.4-year follow-up, 45% of patients had a worsening of disability and 16% of patients with RRMS evolved to SPMS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As clinical outcomes, we selected the EDSS score, the most widely validated MS disability measure, which was used in all prognostic studies, 6 , 7 , 9 - 12 , 14 , 15 and evolution to SPMS, that is associated with a poor prognosis, mostly because of the limited DMT effect in these patients. During the 6.4-year follow-up, 45% of patients had a worsening of disability and 16% of patients with RRMS evolved to SPMS.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, older age, longer disease duration, and higher baseline EDSS score were associated with poorer clinical outcomes. 7 , 37 In particular, a higher baseline EDSS score was retained by multivariable analysis as a predictor of both worsening of disability and evolution to SPMS. This is in line with a recent meta-analysis, indicating baseline EDSS score as the most frequent predictor of future disease course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest discrimination in the included studies was 0.96 and the lowest discrimination was 0.64. These studies showed a good discrimination (0.7-0.8 is regarded as acceptable and 0.8-0.9 is excellent [49]).…”
Section: Discussionmentioning
confidence: 84%
“…Most CPMs in our study were rated high ROB, in line with previous systematic reviews using PROBAST. [16][17][18][19][20] This is inherent to the structure of PROBAST: one incorrectly performed item in one domain determines an overall judgment of high ROB. While the high percentage of models with high ROB might be interpreted as a reflection of the low overall quality of the literature, it might also reflect limitations of the tool.…”
Section: Discussionmentioning
confidence: 99%